Religiosidade e mito na obra de José Carlos Mariátegui e a teologia da libertação - Silva, Adriana Cardoso da [UNESP] (2015)
Among several featured themes developed by the intellectual and militant Peruvian José Carlos Mariátegui (1894-1930) his admirable ability to articulate the different aspects of life in society as the subjective and spiritual dimension of social struggles is evident. These aspects are also evident in Mariátegui latent features in the founding principles of the Theology of Liberation, religious social movement born in Latin America between the decades of 1960 and 1970. You can identify both characteristics of a religious thought, that articulated with the Marxist methodological theoretical framework, inspires the guidance of social practices that unite several popular sectors towards the struggle for social rights, and therefore, for a more just equal society. Given this finding, this research studies the religiousness and myth in Mariátegui, articulated with his revolutionary proposal and compares it to the possible affinities of these concepts with the central assumptions of the Theology of Liberation. Our hypothesis is based on the premise that Mariategui's ideas about religiousness offer different points of instigating contacts in comparison with the Christian movement of the Theology of Liberation. The research takes into account the contours of the historical setting of the time in which the writer dealt with the theme of religion in the 1920s, a period marked by the development of Marxism in Latin America.It is expected a demonstration of the special way in which both do the fusion of religion and politics and that is evident in his writings, revealing, at the same time, his inserts in historical problematic of his times